Public Archaeology in Greece: A Review of the Current State of the Field - Sakellariadi , Anastasia (Ex Novo: Journal of Archaeology, 2021)
As far as archaeology deals with the past in the present, it is already a public endeavour; especially so in southern Europe, where contemporary identities are drawn from ancient cultures, such as the Greek and Roman. In Greece, the political role of the discipline marked antiquities as goods of the people and archaeology as a highly popular discourse. This led to the creation of a state mechanism to manage antiquities for the benefit, but ironically at the exclusion, of the people, in an authoritative top-down approach. In defiance, various actors participate in the public discourse about the past, cultural heritage and its roles today. This paper will review the state of the field by bringing together research in public archaeology in Greece but also non-academic initiatives, such as NGOs and citizen movements. It is argued that public engagement, primarily through museum exhibitions - the most formal and controlled interface between archaeology and non-archaeologists – and cultural events in archaeological sites, is the primary aspect of public archaeology. While public archaeological discourse is overabundant and expansive though, critical research and analysis are lagging and conventional narratives remain broadly unchallenged.